Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pcbi.1004529
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Quantifying the Gain-of-Function Enhancement of IP3 Receptor Gating by Familial Alzheimer’s Disease-Causing Mutants in Presenilins

Abstract: Familial Alzheimer’s disease (FAD)-causing mutant presenilins (PS) interact with inositol 1,4,5-trisphosphate (IP3) receptor (IP3R) Ca2+ release channels resulting in enhanced IP3R channel gating in an amyloid beta (Aβ) production-independent manner. This gain-of-function enhancement of IP3R activity is considered to be the main reason behind the upregulation of intracellular Ca2+ signaling in the presence of optimal and suboptimal stimuli and spontaneous Ca2+ signals observed in cells expressing mutant PS. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…Although we do not simulate whole-cell Ca 2+ waves and oscillations, these events with large amplitude and longer duration occurring at high frequency would most likely trigger global Ca 2+ signals [31]. Consistent with the observations during single channel patch-clamp experiments [4] and recent modeling study [14], our results show that the transition of the channel behavior from gating predominantly in low mode during small events to gating in the intermediate and high modes during large events is due to the significant decrease in τ c with a slight increase in τ o of the channel (Figs. 3e and 5).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Although we do not simulate whole-cell Ca 2+ waves and oscillations, these events with large amplitude and longer duration occurring at high frequency would most likely trigger global Ca 2+ signals [31]. Consistent with the observations during single channel patch-clamp experiments [4] and recent modeling study [14], our results show that the transition of the channel behavior from gating predominantly in low mode during small events to gating in the intermediate and high modes during large events is due to the significant decrease in τ c with a slight increase in τ o of the channel (Figs. 3e and 5).…”
Section: Discussionsupporting
confidence: 84%
“…The behavior of τ o and τ c shown here is again an indication of the change in the modal behavior of the channel. This is reminiscent of experimental data where τ c of the channel was observed to drop from over a second for the low mode to less than 100 ms in intermediate and high modes [4,14]. The τ o on the other hand remained constant within a few milliseconds.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…47. It was concluded that the mutation confers increased sensitivity of the channel to IP 3 , reflected in a change in occupancy of two particular aggregated states of the model (56). We cannot relate this result directly to our model, as although the model of ref.…”
Section: Discussionmentioning
confidence: 80%